Ponte 2016
DOI: 10.21506/j.ponte.2016.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Extracurricular Drama Activities in Foreign Language Teaching

Abstract: Culture is a very valuable part of society. The study of a foreign language not only teaches the language itself, but it also introduces information on another culture, moral values and attitudes. Improving the quality of foreign language education is important. Demanding course content, low proficiency and foreign language learning anxiety discourage students from learning. Difficulty in communicating in the target language reduces their selfconfidence. The use of drama could be one of the possible means to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The findings obtained in the current study are similar to the findings of the previous studies on this topic. Results of not only the current study but also several other studies in this area (Balaban, 2019;Corbett et al, 2011;Çakır, 2008;Çifçi, 2001;De La Cruz, 1995;Dibek, 2003;Eldeniz-Çetin & Avcıoğlu, 2010;Flennoy, 1992;Galante & Thomson, 2017;Gökçearslan-Çiftçi & Altınova, 2017;Göktürk et al, 2020;Kardash & Wright, 1987;Kassab, 1984;Kılıç & Tuncel, 2009;Kuimoval et al, 2016;Pishkar et al, 2017;Saraç, 2007;Shulz, Carpenter, & Turnball, 1991;Warger, 1983) suggested that creative drama method contributed to improve students' speaking skills. Gestures and facial expressions are crucial for conveying messages to be given while speaking because they help messages to be perceived by the receiver.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The findings obtained in the current study are similar to the findings of the previous studies on this topic. Results of not only the current study but also several other studies in this area (Balaban, 2019;Corbett et al, 2011;Çakır, 2008;Çifçi, 2001;De La Cruz, 1995;Dibek, 2003;Eldeniz-Çetin & Avcıoğlu, 2010;Flennoy, 1992;Galante & Thomson, 2017;Gökçearslan-Çiftçi & Altınova, 2017;Göktürk et al, 2020;Kardash & Wright, 1987;Kassab, 1984;Kılıç & Tuncel, 2009;Kuimoval et al, 2016;Pishkar et al, 2017;Saraç, 2007;Shulz, Carpenter, & Turnball, 1991;Warger, 1983) suggested that creative drama method contributed to improve students' speaking skills. Gestures and facial expressions are crucial for conveying messages to be given while speaking because they help messages to be perceived by the receiver.…”
Section: Discussionsupporting
confidence: 62%
“…Creative drama method is highly effective in improving students' speaking skills. There have been several studies revealing that creative drama method helps improve speaking skill (Balaban, 2019;Galante & Thomson, 2017;Gökçearslan-Çiftçi & Altınova, 2017;Göktürk et al, 2020;Kuimoval et al, 2016;Pishkar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They even managed to act them on the "stage" and found it very enjoyable. They confirmed that they would like to have the same activities in the subsequent lessons [15]. The peer-observer also highlighted the students' involvement.…”
mentioning
confidence: 60%
“…Research conducted by Dungs et al, (2017), indicated the benefit of extracurricular activities in fostering the learning experiences of students and their competence in innovation. It mainly depends on the cognition and thinking ability of students to develop competence in innovation.Extracurricular activities like role-playing and drama foster the thinking ability of students and encourage them to empower with imagination and creativity which further enable them to think differently (Kuimova&Polyushko, 2015).Dramatization is also helpful in enhancing critical reasoning, communication, collaboration, and more positive interpersonal relation (Kuimova et al, 2016).Different extracurricular activities enable students to enhance their ability to think innovatively and develop other essential work-related skills. In this way, other such extracurricular activities like science exhibitions or projects nurture critical and creative thinking skills.…”
Section: Introductionmentioning
confidence: 99%